Four-Year Associations of Wish-To-Die Trajectories with Changes in the Frailty of European Citizens Aged 50 and over - De Moraes-Ferrari, G (Elsevier B.V., 2025)
Background: A death wish is a passive ideation about thoughts that suggest dying is better than continuing to live. We investigated the associations of different wish-to-die (WTD) trajectories with changes in frailty over a four-year period in European citizens aged 50 and over. Methods: A longitudinal analysis was conducted with 27,350 participants (13,921 women) from 17 European countries, all aged ≥50 years, who responded to waves 6 and 8 of the Survey of Health, Ageing, and Retirement in Europe (SHARE) project. WTD was assessed by asking, ‘In the last month, have you felt that you would rather be dead?’. Frailty was measured using the SHARE-Frailty (SHARE-FI) questionnaire. Results: A significant effect of time on frailty was observed, with a medium effect size (p < 0.001, ηp2 = 0.08), as well as a significant time × group interaction with a medium effect size (p < 0.001, ηp2 = 0.12). Post hoc analysis revealed a 54.5 % increase in frailty for the continued non-WTD trajectory group over four years. The non-WTD to WTD trajectory group showed a 186.0 % increase in frailty, while the continued WTD group showed a 27.9 % increase in frailty. On the other hand, the group with a trajectory from WTD to non-WTD indicated a reduction in the index of 28.8 %. Conclusions: Emerging WTD may be associated with increased frailty in older age. Conversely, frailty may be reduced among those who exchanged the passive idealization of dying for living. © 2025 Elsevier B.V.